Decontamination of Ultrasound Equipment used for Peripheral Ultrasound-Guided Regional Anaesthesia. Issue 4 (July 2013) - Chuan, A.; Tiong, C.; Maley, M.; Descallar, J.; Ziochos, H.
Portable ultrasound machines are frequently used in operating theatres for peripheral single-shot nerve block procedures. This equipment must be decontaminated by reducing the microbial load to a sufficient level to reduce the risk of nosocomial infection. In our institution we use a simple three-step decontamination protocol utilising 70% isopropyl alcohol as chemical disinfectant. We performed a prospective, quality assurance study to assess the efficacy of this protocol, as it is unclear if this is suitable for disinfecting semi-critical equipment. The primary endpoint was presence of microbial contamination prior to re-use of equipment. Over a four-week period, 120 swabs were taken from multiple sites on our ultrasound machines and linear array transducers for microbial culture. Swabs were taken after decontamination and immediately prior to patient contact. Any pathogenic and environmental bacterial organisms were isolated and identified. No pathogenic organisms were grown from any of the collected swabs. In 85% (n=102) of cultures, no growth was detected. Of the remaining 15% (n=18), commensal organisms commonly found on skin, oral and environmental surfaces were isolated. Our results suggest that our decontamination protocol may be an effective, rapid and cost-effective method of cleaning ultrasound equipment used for peripheral invasive single-shot nerve blocks. Further guidance from national bodies is required to define appropriate cleaning protocols for these machines.